COST AND BENEFIT ANALYSIS ON BREKSI CLIFF THE FORMER LIMESTONE MINING IN YOGYAKARTA - Noto Pamungkas; Sri Suryaningsum (Departemen Manajemen, Universitas Syiah Kuala, 2019)
This study aims to analyze the costs and benefits of the Breksi Cliff which is the former limestone mine in Yogyakarta. The type of data used in this study is primary data. The research is conducted by observation, library research, and in-depth interviews. The object of the research is the Breksi Cliff. The limestone mining activities have been started since the 1980s and now the quality of the limestone is also not suitable for mining and has no economic value. So that local residents creatively create the former limestone mining into a tourist attraction. The Breksi Cliff is a form of creative reclamation in the form of a natural museum that has historical value. The Breksi Cliff offers limestone relief which can also be used as an educational tour. Based on the estimated calculation of income per day if a normal day is IDR10,000,000, then at the weekend of IDR20,500,000, and in the holiday season reaches IDR51,250,000. However, there is no related regulation on retribution. Sleman District Government explained that until now there are no rules that regulate the attractions managed by citizens. It is expected that the Sleman Regency Government will immediately make regulations related to tourist attractions managed by citizens. The retribution can also increase Regional Original Revenue (PADesa). Then infrastructure improvements should be considered more for the safety and comfort of tourists.Key words Tourism, Reclamation, Mining, Cost and Benefit Analysis.